2010
DOI: 10.1111/j.1365-2133.2010.09743.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce Staphylococcus aureus in the management of atopic eczema: an updated Cochrane review

Abstract: We failed to find any evidence that commonly used antistaphylococcal interventions are clinically helpful in people with eczema that is not clinically infected. Their continued use should be questioned in such situations, until better and longer-term studies show clear evidence of clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 26 publications
3
93
0
3
Order By: Relevance
“…However, it must be noted that the cause and effect relationship between skin microbiota dysbiosis and AD remains incompletely elucidated 68. Currently, no evidence of benefit of antimicrobial interventions directed at reduction of Staphylococcus in patients with AD exists, only in secondarily impetiginized AD 69, 70, 71. As multiple studies included in this review indicate that the skin microbiota within an individual patient varies over time 60, 61, 63, 64, there is need for longitudinal, frequent sampling and standard analysis studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be noted that the cause and effect relationship between skin microbiota dysbiosis and AD remains incompletely elucidated 68. Currently, no evidence of benefit of antimicrobial interventions directed at reduction of Staphylococcus in patients with AD exists, only in secondarily impetiginized AD 69, 70, 71. As multiple studies included in this review indicate that the skin microbiota within an individual patient varies over time 60, 61, 63, 64, there is need for longitudinal, frequent sampling and standard analysis studies.…”
Section: Discussionmentioning
confidence: 99%
“…27 A recently updated Cochrane review 28 of antimicrobial interventions for people with eczema, which included 26 studies and 1229 participants, found that most studies were small and of poor quality, and that although there was evidence that interventions reduced the presence of S. aureus on the skin, none of the studies showed any meaningful clinical benefit from antibiotics or other antimicrobial interventions, for either clinically infected or non-infected eczema. The authors concluded that 'Their continued use should be questioned in such situations, until better and longer-term studies show clear evidence of clinical benefit'.…”
Section: Use Of Antimicrobial Treatments For Eczemamentioning
confidence: 99%
“…The authors concluded that 'Their continued use should be questioned in such situations, until better and longer-term studies show clear evidence of clinical benefit'. 28 This is important not only because of the need to identify effective treatments for children with eczema, but also to reduce the use of ineffective treatments currently being prescribed. Clinical experts estimate that children in the UK experience approximately 900,000 eczema flares a year, and that approximately 40% of them are treated with topical antibiotics.…”
Section: Use Of Antimicrobial Treatments For Eczemamentioning
confidence: 99%
“…3 However, a systematic review of antistaphylococcal interventions for AD did not show any convincing clinical improvements in patients with AD, despite quantitative reduction in skin bacterial load. 4 Another hypothesis for AD chronicity is the involvement of immune mechanisms against self-components. Two main observations have led to such a hypothesis.…”
mentioning
confidence: 99%